Tantangan dan Peluang Pendidikan Islam dalam Krisis Multidimensi - Aguk Irawan (Al-Riwayah : Jurnal Kependidikan, 2017)
Education is one of the valuable investments or instrument is in society, nation and state. The increasing of public confidence in Islamic education will affect the globalization and modernization. The implication for the demands and expectations of the public to education, in addition, is to develop the academic potential of science and technology as well the religious values. Thus rest is the basis of moral competence to meet the challenges and opportunities for resolving the multidimensional crisis-facing Indonesia. The solution of problem is Islamic education oriented to the formation of a noble character and a strong personality.